Phyllophorus (Phyllophorus) maculatus, a new species of sea cucumber from the Yellow Sea (Echinodermata: Holothuroidea: Dendrochirotida) - Liao, Yulin; Pawson, David L.; Liu, Wei (Zootaxa, 2007)
Phyllophorus (Phyllophorus) maculatus new species is described from a depth of 22–45 meters near the western edge of the Yellow Sea. The body is cylindrical, with body wall ossicles present only in the anal region. Ossicles are four-pillared tables with low spires and indented disc margin. A revised key to the eleven phyllophorine (Family Phyllophoridae, Subfamily Phyllophorinae) species now known from China is presented.